Mediterranean tephra stratigraphy revisited: Results from a long terrestrial sequence on Lesvos Island, Greece - Margari, V; Pyle, D; Bryant, C; Gibbard, P (2007)
A composite 40.2 m sediment sequence from Megali Limni, Lesvos Island, Greece, spanning the interval from 22 to 62 ka BP, contains six Pleistocene tephra layers, which can be identified on the basis of their major and trace elemental compositions. The youngest tephra deposit correlates with the 22 ka Y-2 marker, erupted during the Cape Riva eruption of Santorini. The second tephra originates from the Campanian area in Italy and corresponds to the Campanian Ignimbrite eruption (the 39 ka Y-5 marker). The next two layers are compositionally identical, and originate from Eastern islands of the Hellenic Arc; they could potentially correspond to the Upper and Lower Pumice eruptions of Nisyros or some other previously unidentified eruption from Yali. The fifth stratum corresponds to the Y-6 marker, which erupted during the Green Tuff eruption of the Pantelleria Island. The source of the last tephra layer is either the Yali-Nisyros complex or Central Anatolia; no specific corresponding eruption has yet been found. Long distal tephra sequences within terrestrial settings are rare in the eastern Mediterranean and the Megali Limni record contains the most complete sequence to date. Moreover, its age model, based on independent chronologies such as AMS and conventional radiocarbon dates and high-resolution pollen stratigraphy, provides new ages for these eruptions and places them within the context of the millennial-scale palaeoenvironmental variability of the last glacial period. Finally, the recognition of the Pantelleria tephra in this locality considerably extends the confirmed Northerly and Easterly distribution of this widespread and distinctive unit, while the existence of the Nisyros-Yali tephras on Lesvos refutes the current belief of limited tephra dispersal and small magnitude of these eruptions. © 2007 Elsevier B.V. All rights reserved.